Підприємство як цілісний майновий комплекс: суб’єкт чи об’єкт прав? - Ковальчук, В.; Kovalchuk, V. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
Підприємство як цілісний майновий комплекс є тим правовим явищем, яке не має однозначного трактування у юридичній літературі, що зумовлено неточною регламентацією його правового статусу у чинному законодавстві України. В статті висвітлюються законодавчі колізії у правовому статусі підприємства як цілісного майнового комплексу, що є наслідком характеристики підприємства і у якості суб’єкта, і у якості об’єкта прав. The article deals with the controversy definition of enterprise nature as the civil the right’s subject or object that appeared among jurists at the end of 19 and at the beginning of 20 centuries. This problem is still relevant and causes by the incorrect regulation of the legal status of the enterprise as an integral property complex according to the current legislation of Ukraine. The legal conflicts of the enterprise legal status as an integral property complex that is a consequence of the characteristics of the enterprise and as right’s subject and as object is highlighted. The correlation between «single property complex» and «property position complex» is analysed. The author comes to the conclusion that these concepts are identical according to the Civil Code of Ukraine provision but in different legal norms they use though the legal construction of «integral (single) property complex». The legal position of company’s and integral (single) property complex of civil rights’ individual objects as well as the recognition of the position only the status of entity without recognizing the status of the object has been investigated.
Enterprise as the Property Complex: the Right’s Subject or Object?
Keywords: підприємство; цілісний майновий комплекс; об’єкт прав; суб’єкт прав; enterprise; complex entire property; the right’s object; the right’s subject